16S rRNA gene sequencing reveals altered composition of gut microbiota in postoperative individuals with renal stones. (1st August 2022) - Deng, Qiong; Wang, Zhu; Wang, Jieyan; Zhang, Jianwen; Zhang, Ying; Liang, Hui
Abstract: Renal stones are a common urological disease with high prevalence and recurrence rates. Characterizing gut microbiome profiles of first‐onset renal calculi patients, both before and after surgery, may provide valuable insights and identify potential biomarkers for the disease. In this study, we explored the associations between the gut microbiome and renal stone formation using 16S ribosomal RNA (rRNA) gene sequencing. In brief, 20 patients were recruited, and information on health and eating habits within the previous 1–3 months was collected upon admission. A total of 493 operational taxonomic units (OTUs) were detected in 40 specimens, with an average of 67, 888 ± 827 reads per sample. The results of OTU‐based partial least squares discriminant analysis (PLS‐DA) analysis showed differences between RS1 (fecal specimen before surgery) and RS2 (one month later after surgery) groups, with a significantly higher level of OTU7 in the RS2 group. Taxonomy‑based comparisons of the gut microbiome showed differences in the flora composition, with the prevalence of Enterobacteriales, Enterobacteriaceae, Gammaproteobacteria and Escherichia being higher in the RS2 group and the prevalence of Pseudomonadaceae, Pseudomonadales and Pseudomonas being higher in the RS1 group. Correlation analysis showed that an increased prevalence of Enterobacteriaceae, Gammaproteobacteria and Escherichia associated with a decreased level of urea, and a decreased creatinine level was correlated with an increased prevalence of Escherichia . These data strongly suggest that the gut microbiome plays an important role in kidney stone formation, and these findings may provide new insights for the prevention, diagnosis, and treatment of renal stones. Abstract: Significance and Impact of Study: 1. Faecal samples before surgery (RS1) and one month after surgery (RS2) showed difference in flora composition, with the prevalence of Enterobacteriales, Enterobacteriaceae, Gammaproteobacteria and Escherichia being higher in the RS2 group and the prevalence of Pseudomonadaceae, Pseudomonadales and Pseudomonas being higher in the RS1 group. 2. The increased prevalence of Enterobacteriaceae, Gammaproteobacteria and Escherichia were associated with a decreased level of urea, and a decreased creatinine level was correlated with an increased prevalence of Escherichia .